A novel Klebsiella pneumoniae diguanylate cyclase contributes to intestinal cell adhesion, biofilm formation, iron utilization, and in vivo virulence by gastrointestinal infection - Chun-Ru Hsu; Ya-Ling Huang; Pang-Hung Hsu; Chen-Hsiu Huang; Yu-Chieh Huang; Ming-Ti Kao; You-Wei Ye (Virulence)
Klebsiella pneumoniae is responsible for various infections such as bacteremia, urinary tract infections, pneumonia, and liver abscesses. Multidrug-resistant K. pneumoniae infections pose a critical public health threat, often associated with high mortality rates. The emergence of hypervirulent K. pneumoniae has also raised global health concerns due to its invasive disease potential. Clinical studies suggest intestinal colonization by K. pneumoniae as a risk factor for subsequent infections, but the underlying mechanisms remain unclear. Cyclic di-GMP (c-di-GMP), a bacterial signaling molecule synthesized by diguanylate cyclases (DGCs), controls various cellular processes and is absent in higher organisms, making it an attractive target for antimicrobial development. In this study, we identified a novel DGC, designated as DgcG, in K. pneumoniae, which plays a pivotal role in gastrointestinal colonization and pathogenesis. Using genetic deletion and complementation analyses in a bacteremia and liver abscesses-inducing strain Ca0437, we observed that DgcG promoted intestinal adherence, biofilm formation, iron utilization, and in vivo virulence. RT-qPCR showed that DgcG regulated genes involved in type 3 fimbrial expression and iron transport. In a gastrointestinal infection model of female BALB/cByl mice, dgcG deletion significantly reduced host mortality and bacterial load in the liver, spleen, and intestines, underscoring its role in enhancing bacterial survival and dissemination. Additionally, dgcG gene was found highly conserved and prevalent among diverse K. pneumoniae isolates. These findings provide new insights into c-di-GMP-mediated virulence regulation in K. pneumoniae and highlight DgcG as a potential therapeutic target for controlling K. pneumoniae infections, especially amidst the growing global antimicrobial resistance crisis.